Knowledge, Awareness, and Practice Towards Blood Donation Among UTHM Diploma Students - Mhd Sahruddin, Anes Aleeya Zulaikha; Ismail, Nurin Sofea; Nawi, Adnin Afifi (2025)
This study is conducted to compare the level of knowledge, attitude, and practice level of blood donation between male and female students in diploma programs in UTHM Pagoh. In this study, the significance difference of knowledge, attitude and practices of blood donation based on gender was also determined. Apart from that, the purpose of this study is to determine the relationship between knowledge, attitude, and practice level of blood donation among diploma students in UTHM. A cross-sectional survey was distributed to 200 diploma students in UTHM Pagoh which consists of seven courses: Diploma in Applied Science, Diploma in Chemical Engineering Technology, Diploma in Electrical Engineering, Diploma in Civil Engineering, Diploma in Mechanical Engineering, Diploma in Information Technology and Diploma in Animation Technology using a Google Form questionnaire. Data collected was analysed by using Statistical Package for Social Sciences (SPSS) version 27. The result shows that female students have more knowledge, attitude, and practice level of blood donation than male students. Based on gender, there were no significant difference in terms of knowledge, attitude and practices of blood donation among UTHM diploma students. Most of female and male of diploma students have a basic knowledge but poor attitude toward blood donation. Moreover, they might have a basic knowledge regarding blood donation but did not apply them in real life. They may have good attitude toward blood donation, but they do not practice the proper way of blood donation. Further research needs to be conducted to find effective ways to spread awareness about the blood donation. It can increase the level of knowledge, attitude, and practice (KAP) towards blood donation among diploma UTHM students.